Economic Contributions of the Dairy Farming and Dairy Product Manufacturing Industries in the Southeast United States in 2005 - Thomas J. Stevens; Alan W. Hodges; W. David Mulkey; Richard L. Kilmer (EDIS)
FE731, a 32-page analysis by Thomas J. Stevens, Alan W. Hodges, W. David Mulkey, and Richard L. Kilmer, estimates the economic contributions of the dairy farm production and dairy product manufacturing industries in five southeastern states (Alabama, Florida, Georgia, South Carolina, and Tennessee) during 2005. Includes references. Published by the UF Department of Food and Resource Economics, August 2008.